DIGITAL SERVICES TAX REGULATION AND WTO NON-DISCRIMINATION PRINCIPLE: IS THE DECK STACKED? - Elisabet, Mutiara; Dewi, Yetty Komalasari (Indonesian Journal of International Law, 2021)
A growing debate on the imposition of digital services tax emerged as one of the latest trade war battlegrounds. Indonesia and the European Union (EU) are among the countries that have taken unilateral actions to implement digital services tax. This paper examines (i) digital services tax regulation in Indonesia and the EU and (ii) whether the digital services tax regulation violates the non-discrimination principles of WTO according to the GATS. By comparing the statutory and practice of digital services tax in Indonesia and the EU, this work concludes that firstly, digital services tax in Indonesia is regulated by law, which implements significant economic presence (SEP) criteria. In the EU, digital services tax is regulated through the Council Directives and implements ring-fencing method as well as SEP criteria. Secondly, the non-discrimination principles in the GATS are promulgated in Article II concerning Most-Favored Nation Treatment and Article XVII concerning National Treatment as well as relevant jurisprudence of WTO case laws. Indonesia and the EU’s digital services tax regulation are not discriminatory, because based on existing indicators, the existence of both de jure and de facto discrimination is not proven. This paper suggests that in the event that there are member states who decide to challenge the measures to the WTO, Indonesia and the EU should provide evidence that shows the absence of unfavorable treatment of certain WTO member states in digital services tax practices by Indonesia and the EU.